2019
DOI: 10.7554/elife.48789
|View full text |Cite
|
Sign up to set email alerts
|

The Caenorhabditis elegans Tubby homolog dynamically modulates olfactory cilia membrane morphogenesis and phospholipid composition

Abstract: Plasticity in sensory signaling is partly mediated via regulated trafficking of signaling molecules to and from primary cilia. Tubby-related proteins regulate ciliary protein transport; however, their roles in remodeling cilia properties are not fully understood. We find that the C. elegans TUB-1 Tubby homolog regulates membrane morphogenesis and signaling protein transport in specialized sensory cilia. In particular, TUB-1 is essential for sensory signaling-dependent reshaping of olfactory cilia morphology. W… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 139 publications
1
16
0
Order By: Relevance
“…In the absence of Inpp5e , PI(4,5)P2 accumulates in the cilium, while ciliary PI(4)P levels drop ( Chávez et al, 2015 ; Garcia-Gonzalo et al, 2015 ; Figure 2C ). Similarly, in fly and worm sensory neurons, loss of INPP5E orthologs leads to increased PI(4,5)P2 levels in cilia ( Park et al, 2015 ; DiTirro et al, 2019 ). Together, these findings are consistent with the model that PI(4,5)P2 diffuses laterally from the plasma to the ciliary membrane, where it is converted to PI(4)P by Inpp5e.…”
Section: Lipid Composition Of the Ciliary Membranementioning
confidence: 98%
See 3 more Smart Citations
“…In the absence of Inpp5e , PI(4,5)P2 accumulates in the cilium, while ciliary PI(4)P levels drop ( Chávez et al, 2015 ; Garcia-Gonzalo et al, 2015 ; Figure 2C ). Similarly, in fly and worm sensory neurons, loss of INPP5E orthologs leads to increased PI(4,5)P2 levels in cilia ( Park et al, 2015 ; DiTirro et al, 2019 ). Together, these findings are consistent with the model that PI(4,5)P2 diffuses laterally from the plasma to the ciliary membrane, where it is converted to PI(4)P by Inpp5e.…”
Section: Lipid Composition Of the Ciliary Membranementioning
confidence: 98%
“…In contrast, phosphatidylinositol-4,5-bisphosphate [PI(4,5)P2] is largely depleted from the ciliary membrane in mammals, Caenorhabditis elegans , Drosophila melanogaster , and Trypanosoma brucei . Instead, PI(4,5)P2 localizes to distinct membrane domains at the cilia base creating a sharp boundary in PPI composition ( Chávez et al, 2015 ; Garcia-Gonzalo et al, 2015 ; Jensen et al, 2015 ; Park et al, 2015 ; DiTirro et al, 2019 ; Dyson et al, 2017 ; Figure 2A ). In retinal pigmented epithelial cells and primary mouse embryonic fibroblasts, PI(4,5)P2 is concentrated at the TZ, which also contains phosphatidylinositol-3,4,5-trisphosphate [PI(3,4,5)P3] ( Dyson et al, 2017 ).…”
Section: Lipid Composition Of the Ciliary Membranementioning
confidence: 99%
See 2 more Smart Citations
“…So far, TULP proteins have a well-established role in the selective transport of G-proteincoupled receptors (GPCRs), channels, enzymes, and signaling proteins into cilia (Badgandi et al, 2017;DiTirro et al, 2019;Han et al, 2019;Legué and Liem, 2019;Sun et al, 2012). Intriguingly, a recent study showed that E-Syt3 is specifically expressed in hypothalamic nuclei involved in energy homeostasis and food intake (Zhang et al, 2020), and thus shows a striking overlap with neuronal tubby expression (including the arcuate nucleus) (Kleyn et al, 1996).…”
Section: Biological Function Of Tubby (And Tulp) Localizationmentioning
confidence: 99%